Cantando a Reforma Protestante : o protagonismo das mulheres no início do movimento - Ramos, Manuel Machado Goncalves (2023)
The present work investigates the potential of the song as an effective didactic resource in the teaching of History, with the Protestant Reformation as its thematic focus, focusing on the performance and influence of women reformers and apologists Argula von Grumbach and Marie Dentière. The structuring concepts of the theoretical framework were articulated based on the references of MacGrath (2007, 2012, 2014), Lindberg (2017), Delumeau (1989), Salviano (2021), Napolitano (2002), Bitterncourt (2011), Brum (2020) , Morais (2017), among others. As for the final product, a set of four workshops were developed and implemented aimed at the 7th year classes of the Escola Municipal do Ensino Fundamental Professor Lynaldo Cavalcanti in Albuquerque. The overall purpose of these workshops was to reflect on and evaluate the effectiveness of song analysis as a pedagogical tool in the context of history teaching. Furthermore, we aim to guide and analyze parodies created by the students themselves. The central theme addressed in the offices, as well as in the production of parodies, was the Protestant Reformation, with an emphasis on the notable figure of the reformer Argula von Grumbach.